ANALISIS BENTANG ALAM KUARTER DAERAH CIREBON BERDASARKAN GENESANYA - Hidayat, Suyatman; Lumbanatu, Ungkap M (Pusat Survei Geologi, 2010)
The research is to study geomorphology of Cirebon area to understand its genetic process. A remote sensing analysis and field observations resulted in seven landform units. These are, Marine Origin, Fluvio-Marine, Fluvial, Volcanic, Fluvio-volcanic, Denudated, and Structural Origin. It reveals that development of landscape features of the investegated area was strongly affected by marine and fluvial processes.Keywords: landscape, landform, marine, river